Evaluation subgroups of a map and the rationalized G-sequence - Maphane, Oteng (Armenian Journal of Mathematics, 2023)
In this paper, we determine, in terms of the Sullivan models, rational evaluation subgroups of the inclusion C P(n)C P(n+k) between complex projective spaces and, more generally, the G -sequence of the homotopy monomorphism ι: XY between simply connected formal homogeneous spaces for which π_*(Y)Q is finite-dimensional. Editorial Board’s note. We inform our readers that J.-B. Gatsinzi mentions in his work, published in Armen. J. Math. vol. 15, no. 9, 2023, that O. Maphane’s paper contains a mistake. According to Gatsinzi, his Corollary 1 corrects Theorem 2.2 of the current paper. We contacted Maphane on this issue, and he agreed with Gatzinzi’s statement.